PEMBUATAN GAME 2D PLATFORM “BOLA” BERBASIS WEBSITE - Anthony Anthony; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
This game was created using Unity game engine with C# as its programming language. The goal of this game is to complete all the stages with lowest time. This game got 3 characters: red ball, hardened ball and smollie ball. At each stage, player will face obstacles such as spike, spike ball, and hidden spike. Testing is done by blackbox testing, alpha testing by the supervisor, and beta testing by 38 respondents through a questionnaire. The test results show that game Bola can make players enjoy it and encourage them to play again.